Dietary Enterococcus faecalis LAB31 Improves Growth Performance, Reduces Diarrhea, and Increases Fecal Lactobacillus Number of Weaned Piglets - Hu, Yuanliang; Dun, Yaohao; Li, Shenao; Zhang, Dongxiao; Peng, Nan; Zhao, Shumiao; Liang, Yunxiang (PloS one, 2015)
Lactic acid bacteria (LAB) have been shown to enhance performance of weaned piglets. However, few studies have reported the addition of LAB Enterococcus faecalis as alternatives to growth promoting antibiotics for weaned piglets. This study evaluated the effects of dietary E. faecalis LAB31 on the growth performance, diarrhea incidence, blood parameters, fecal bacterial and Lactobacillus communities in weaned piglets. A total of 360 piglets weaned at 26 ± 2 days of age were randomly allotted to 5 groups (20 pens, with 4 pens for each group) for a trial of 28 days: group N (negative control, without antibiotics or probiotics); group P (Neomycin sulfate, 100 mg/kg feed); groups L, M and H (supplemented with E. faecalis LAB31 0.5×109, 1.0×109, and 2.5×109 CFU/kg feed, respectively). Average daily gain and feed conversion efficiency were found to be higher in group H than in group N, and showed significant differences between group H and group P (P0 < 0.05). Furthermore, groups H and P had a lower diarrhea index than the other three groups (P0 < 0.05). Denaturing gradient gel electrophoresis (DGGE) showed that the application of probiotics to the diet changed the bacterial community, with a higher bacterial diversity in group M than in the other four groups. Real-time PCR revealed that the relative number of Lactobacillus increased by addition of probiotics, and was higher in group H than in group N (P0 < 0.05). However, group-specific PCR-DGGE showed no obvious difference among the five groups in Lactobacillus composition and diversity. Therefore, the dietary addition of E. faecalis LAB31 can improve growth performance, reduce diarrhea, and increase the relative number of Lactobacillus in feces of weaned piglets.